A soft‐switching inverting high step‐down converter with a pair of coupled inductors and self‐driven synchronous rectifier. Issue 15 (21st September 2021) - Hosseinabadi, Farzad; Soleymani, Behzad; Adib, Ehsan; Islam, Md. Rabiul; Farzanehfard, Hosein; Kouzani, Abbas Z.; Mahmud, M. A. Parvez
Abstract: In this paper, a non‐isolated coupled‐inductor high step‐down converter with extended duty cycle is proposed, which operates under discontinuous conduction mode. The soft‐switching condition is provided for all the switches and diodes, which results in the reduction of the switching losses, and the losses related to diode reverse recovery problem. Also, a self‐drive circuit is used to automatically generate the ON and OFF gate signals of the synchronous rectifier, which recovers the gate energy and reduces the complexity. In this topology, only a single coupled inductor is proposed which decreases the size and cost of the proposed converter. A 200 W laboratory prototype is implemented, and its results confirm the validity of theoretical analysis and advantages of the proposed converter over previous structures.